Contents of Rare Earth Elements in Orange from Rare Earth Mining Area of Wuxun, China - Cai, Dingjian; Rui, Yukui (Asian Journal of Chemistry, 2013)
Concentrations of rare earth elements in oranges from Xunwu county of Jiangxi province (rare-earth mining area) was determined by ICP-MS to investigate the effects of rare earth elements mining on food safety. The results showed that the contents of all detected rare earth elements in oranges from Xunwu county were much higher than the contents in those from Nanfeng county and were several times of that of other fruits, which proved that rare earth mining significantly affected the ingredient of food. But the contents of rare earth elements were still much lower than the national hygiene standards of rare earth limits in food.